(Lioret, 2009). (1st January 2020) - Stehle, Maria; Weber, Beverly
This article examines the role of Europe as gift in Lioret's Welcome (2009) and Peren's Die Farbe des Ozeans (2011) by focusing on gestures of welcome extended by white European characters to undocumented migrants. In both films, these gestures include gifts, in the form of money, shelter or skills taught, that play an important narrative role, but subordinate refugee characters' lives and stories to the emotional needs of white European 'givers'. In this way gifts of welcome become violent acts that reinforce European assumptions about European political and epistemological superiority, and paper over the existence of colonial and racist violence that continues to produce precarious lives.